Cuproptosis-related genes signature and validation of differential expression and the potential targeting drugs in temporal lobe epilepsy - Yang, Xiaolin; Zhang, Xiaoqing; Shen, Kaifeng; Wang, Zhongke; Liu, Guolong; Huang, Kaixuan; He, Zeng; Li, Yang; Hou, Zhi; Lv, Shengqing; Zhang, Chunqing; Yang, Hui; et al. (Frontiers in Pharmacology, 2023)
Temporal lobe epilepsy (TLE) is the most common subtype of epilepsy in adults and is characterized by neuronal loss, gliosis, and sprouting mossy fibers in the hippocampus. But the mechanism underlying neuronal loss has not been fully elucidated. A new programmed cell death, cuproptosis, has recently been discovered; however, its role in TLE is not clear. We detected the tissue copper ion concentration of the hippocampus. Next, using the Sample dataset and E-MTAB-3123 dataset, we analyzed the features of 12 cuproptosis-related genes in TLEs and controls using the bioinformatics tools. Then, the expression of the key cuproptosis genes were confirmed using real-time PCR and immunohistochemical staining (IHC). Finally, the Enrichr database was used to screen the small molecules and drugs targeting key cuproptosis genes in TLE. The results showed the Sample dataset had four differentially expressed cuproptosis-related genes (DECRGs; LIPT1, GLS, PDHA1, and CDKN2A) and the E-MTAB-3123 dataset had seven DECRGs (LIPT1, DLD, FDX1, GLS, PDHB, PDHA1, and DLAT). However, only LIPT1 was consistently upregulated in both datasets. In addition, these DECRGs are involved in the TCA cycle and pyruvate metabolism which are critical for cell cuproptosis and various immune cell infiltrations in the hippocampus of TLE, especially macrophages and T cells. Besides, DECRGs were related to the abundance of most infiltered immune cells in the acute phase of TLE, while the association was significantly weakened in the latent phase, and in the chronic phase, DECRGs were associated with the abundance of many subclasses of T cells. Moreover, LIPT1, FDX1, DLD, and PDHB were related to the identification of TLE. Further, the PCR and IHC confirmed that the expression of LIPT1 and FDX1 was upregulated in TLE compared with controls. Furthermore, we found that chlorzoxazone and piperlongumine inhibited cell cuproptosis by targeting LIPT1, FDX1, DLD, and PDHB using the Enrichr database. In summary, these results suggest that cuproptosis is directly related to TLE, the signature of cuproptosis-related genes provides new clues for exploring the roles of neuronal death in TLE, and LIPT1 and FDX1 may be potential targets of neuronal cuproptosis for controlling seizure and progression of TLE.